2003
DOI: 10.1001/jama.290.13.1739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen Plus Progestin on Gynecologic Cancers and Associated Diagnostic Procedures<SUBTITLE>The Women's Health Initiative Randomized Trial</SUBTITLE>

Abstract: OR YEARS, THERE HAS BEEN CONcern about possible associations of gynecologic malignancies with postmenopausal hormone therapy. The development of endometrial hyperplasia and endometrial cancer with unopposed estrogen is well recognized. To reduce or avoid this complication, progestin has been added, 1-3 although results from randomized trials are extremely limited. These concerns have created a need for reasonable monitoring guidelines to follow-up women who experience vaginal bleeding while taking estrogen plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
264
2
23

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(304 citation statements)
references
References 31 publications
9
264
2
23
Order By: Relevance
“…Likewise, many observational studies have not supported an association [5,11,15,29,31,33]. Two large cohort studies and one randomized controlled trial have suggested an increased risk of 50% in association with EP use [8,13,14]. In comparison, the most recent cohort study, the Million Women study, detected a statistically significant 10% increased risk [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, many observational studies have not supported an association [5,11,15,29,31,33]. Two large cohort studies and one randomized controlled trial have suggested an increased risk of 50% in association with EP use [8,13,14]. In comparison, the most recent cohort study, the Million Women study, detected a statistically significant 10% increased risk [7].…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies conducted in the U.S. [5,11,[13][14][15]31,32], Australia [33], Norway [8], Sweden [29], and U.K [7] have been inconclusive regarding the relationship between EP and ovarian cancer. Overall, we detected no associations with EP use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Women's Health Initiative, the parent study for WHIMS (Shumaker et al 2003, was a multicenter, randomized, double-blind, placebo-controlled trial designed to assess effects of a commonly prescribed oral HT on cardiovascular disease, breast cancer, and other health outcomes (Anderson et al 2003;Rossouw et al 2002). Active treatment was with combined HT for women with a uterus [conjugated equine estrogens (CEE) 0.625 mg/day with MPA 2.5 mg/day as a continuous combined preparation; CEE+MPA trial) or with estrogen alone (CEE 0.625 mg/day; CEE-alone trial) for women without a uterus.…”
Section: Women's Health Initiative Memory Studymentioning
confidence: 99%
“…2,18 The same studies simultaneously confirmed the two well-known side effects of HRT: increased risk of breast cancer, 2,[19][20][21][22] which rises with the duration of HRT 19 and is substantially greater in oestrogen-progestogen combined HRT; 20 and increased risk of thromboembolism, 2,13,23,24 which seems to be highest in the first year of use. 24 Other reported side effects were increased risk of gall bladder diseases, 13 increased risk of ovarian cancer with continuous use of combined HRT 25 and increased risk of dementia in women aged 65 and older. 26 These new findings have caused much uncertainty among women and their doctors regarding the usage of HRT.…”
Section: Introductionmentioning
confidence: 99%